Preparation process of sulphoaluminate cement material with high slump retention performance
Patent Information
- Application Number
- CN202611187185.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-08-06
AI Technical Summary
然而,由于硫铝酸盐水泥水化极快、早期水化产物钙矾石形成速率快、形成量多,导致水泥颗粒表面电荷、吸附位点变化快,聚羧酸减水剂分子易脱附,造成水泥浆体的坍落度快速损失
本发明先利用硅烷偶联剂对硫铝酸盐水泥进行处理,使水泥颗粒表面接枝偶联剂包覆层,然后在其表面负载四丁基氯化膦层后利用其中心氮原子携带的正电荷与所述聚羧酸减水剂分子上羧基间的静电作用使聚羧酸减水剂分布在水泥颗粒表面。一方面,这种结构利用所述硅烷偶联剂适当的疏水屏蔽作用可以有效降低硫铝酸盐水泥在拌和初期与水接触后释放大量硫酸根离子和铝相组分,从而干扰聚羧酸减水剂的静电斥力+空间位阻效应,造成水泥浆料的坍落度加快损失。另一方面,所述四丁基氯化膦可对聚羧酸减水剂起到静电锚固作用,再加上通过偶联剂包覆层还可以通过抑制硫铝酸盐水泥在拌和初期的水化反应造成的水泥颗粒表面电荷、吸附位点变化快的问题,从而可以有效缓解因此造成的减少聚羧酸减水剂分子容易从水泥颗粒表面脱落的问题,使聚羧酸减水剂分子能够更好地发挥作用,进而使硫铝酸盐水泥浆料在拌和初期与输送阶段具有更好的保坍性能。
Smart Images

Figure CN122705244B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of cement-based building materials technology, specifically to a preparation process for a sulfoaluminate cement material with high slump retention performance. Background Technology
[0002] The information disclosed in the background section of this invention is intended only to enhance the understanding of the overall background of this invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
[0003] Sulfoaluminate cement is a hydraulic cementitious material with excellent properties such as early strength, rapid hardening, and low alkalinity. It is produced by calcining anhydrous calcium sulfoaluminate and dicalcium silicate clinker at a lower temperature than traditional silicate cement, using limestone, bauxite, and gypsum as raw materials. Appropriate amounts of admixtures (such as gypsum and limestone) are added and ground together. Furthermore, the production of sulfoaluminate cement has a significant low-carbon advantage compared to traditional silicate cement. In terms of durability, sulfoaluminate cement also performs excellently, with superior frost resistance, impermeability, and corrosion resistance compared to ordinary silicate cement. However, sulfoaluminate cement also has certain limitations. Studies have shown that this cement suffers from drawbacks such as late-stage strength reduction and large drying shrinkage, which limits its widespread application and promotion in civil engineering.
[0004] Furthermore, the rapid setting speed of sulfoaluminate cement often makes it difficult for concrete materials to meet the requirements of long-distance transportation and on-site pouring. Water-reducing agents are a key technological means to overcome this problem. Polycarboxylate superplasticizers are commonly used comb-like superplasticizers that can adsorb onto the surface of cement particles, dispersing them through electrostatic repulsion and other effects, thereby improving the fluidity of the cement paste. However, due to the extremely rapid hydration of sulfoaluminate cement, the rapid formation rate and large quantity of the early hydration product ettringite, the surface charge and adsorption sites of cement particles change rapidly, making polycarboxylate superplasticizer molecules prone to desorption, resulting in a rapid loss of slump in the cement paste. In addition, the insufficient adsorption stability of polycarboxylate superplasticizers on sulfoaluminate cement, a fast-setting type of cement, and the interference of sulfate and aluminum phase components in sulfoaluminate cement with the electrostatic repulsion and steric hindrance effects of polycarboxylate superplasticizers, further exacerbate slump loss. Summary of the Invention
[0005] To address the aforementioned problems, this invention provides a preparation process for sulfoaluminate cement materials with high slump retention performance, effectively overcoming the problem of insufficient compatibility between sulfoaluminate cement particles and polycarboxylate superplasticizers, which limits the improvement effect of polycarboxylate superplasticizers on the slump retention performance of sulfoaluminate cement. Specifically, the technical solution of this invention is as follows.
[0006] A preparation process for a sulfoaluminate cement material with high slump retention includes the following steps: (1) Mix sulfoaluminate cement powder with anhydrous ethanol containing silane coupling agent evenly, and then dry to obtain pretreated sulfoaluminate cement.
[0007] (2) The pretreated sulfoaluminate cement is mixed evenly with anhydrous ethanol containing tetrabutylphosphine chloride, dried, and then sprayed with polycarboxylate superplasticizer and mixed evenly to obtain modified sulfoaluminate cement.
[0008] (3) Using the modified sulfoaluminate cement, fine aggregate, inorganic filler and retarder as raw materials, mix them with mixing water to obtain sulfoaluminate cement material.
[0009] Further, in step (1), the ratio of the sulfoaluminate cement powder to the anhydrous ethanol solution is 1g: 2~3.5mL. Optionally, the mass fraction of the silane coupling agent in the anhydrous ethanol solution is 0.12~0.18%.
[0010] Further, in step (1), the silane coupling agent includes at least one of KH-550, KH-560, A-171, A-172, etc.
[0011] Further, in step (2), the ratio of the pretreated sulfoaluminate cement to anhydrous ethanol solution is 1g:1~2mL. Optionally, the mass fraction of tetrabutylphosphine chloride in the anhydrous ethanol solution is 0.06~0.075%.
[0012] Further, in step (2), the polycarboxylate superplasticizer is 1.5 to 2.2% of the mass of the pretreated sulfoaluminate cement.
[0013] Further, in step (3), the proportions of each component are: 100-115 parts by weight of modified sulfoaluminate cement, 145-170 parts by weight of fine aggregate, 10-15 parts by weight of inorganic filler, 0.05-0.2 parts by weight of retarder, and 44-53 parts by weight of mixing water.
[0014] Further, in step (3), the inorganic filler includes at least one of fly ash, calcium carbonate powder, mica powder, etc. Optionally, the fineness of the inorganic filler is 300~500 mesh.
[0015] Further, in step (3), the retarder includes at least one of borax, sodium hexametaphosphate, sodium pyrophosphate, sodium gluconate, sodium citrate, etc.
[0016] Further, in step (3), the raw material also includes 0.7-1.1% by weight of crack-resistant fiber. Preferably, the crack-resistant fiber is prepared by the following method: (i) Polyvinyl alcohol fiber and / or polyacrylonitrile fiber are mixed evenly with imidazole acetate solution and allowed to stand, then the fiber is separated and washed to obtain pretreated fiber. (ii) The pretreated fiber is then immersed in a mixture of tetraethyl orthosilicate and ethanol, and the resulting impregnated fiber is mixed with an alkaline solution and heated and kept at a constant temperature; after completion, the fiber is separated, washed, and dried to obtain the crack-resistant fiber.
[0017] Further, in step (i), the ratio of polyvinyl alcohol fiber and / or polyacrylonitrile fiber to imidazole acetate solution is 1g:0.2~0.3mL. Optionally, the mass fraction of the imidazole acetate solution is 1.7~2.5%.
[0018] Further, in step (i), the imidazole acetate includes at least one of 1-ethyl-3-methylimidazolium acetate, 1-butyl-3-methylimidazolium acetate, 1-allyl-3-methylimidazolium acetate, etc.
[0019] Further, in step (i), the length of the polyvinyl alcohol fiber and / or polyacrylonitrile fiber is 10~30 mm, and the diameter is 0.1~0.15 mm. Optionally, the settling time is 8~12 min.
[0020] Further, in step (ii), the ratio of the pretreated fiber to the tetraethyl orthosilicate-ethanol mixture is 1g:10~25mL. Optionally, the volume ratio of tetraethyl orthosilicate to ethanol is 1:3~4.
[0021] Further, in step (ii), the immersion treatment time is 45~55 min.
[0022] Further, in step (ii), the ratio of the impregnated fiber to the alkaline solution is 1g: 6.5~10mL. Optionally, the concentration of the alkaline solution is 0.05~0.1mol / L.
[0023] Further, in step (ii), the alkaline solution includes at least one of sodium hydroxide solution, potassium hydroxide solution, ammonia water, etc.
[0024] Further, in step (ii), the heating and heat preservation temperature is 60~80℃, and the standing time is 1~1.5 hours.
[0025] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects: This invention first treats sulfoaluminate cement with a silane coupling agent to graft a coupling agent coating layer onto the surface of the cement particles. Then, a tetrabutylphosphine chloride layer is loaded onto the surface, and the electrostatic interaction between the positive charge carried by the central nitrogen atom and the carboxyl groups on the polycarboxylate superplasticizer molecule causes the polycarboxylate superplasticizer to distribute on the surface of the cement particles. On one hand, this structure, utilizing the appropriate hydrophobic shielding effect of the silane coupling agent, can effectively reduce the release of large amounts of sulfate ions and aluminum phase components from sulfoaluminate cement upon initial contact with water during mixing. This would interfere with the electrostatic repulsion and steric hindrance effect of the polycarboxylate superplasticizer, leading to accelerated slump loss in the cement slurry. On the other hand, the tetrabutylphosphine chloride can electrostatically anchor the polycarboxylate superplasticizer. In addition, the coupling agent coating layer can also suppress the rapid changes in surface charge and adsorption sites of cement particles caused by the hydration reaction of sulfoaluminate cement in the early stage of mixing. This can effectively alleviate the problem of polycarboxylate superplasticizer molecules easily falling off the surface of cement particles, allowing the polycarboxylate superplasticizer molecules to play a better role. As a result, the sulfoaluminate cement slurry has better slump retention performance in the early stage of mixing and transportation.
[0026] Furthermore, the sulfoaluminate cement material of this invention also possesses crack-resistant fibers, which can effectively overcome the problem of reduced strength in the later stages of hardening caused by large drying shrinkage during the hardening process of sulfoaluminate cement. To this end, this invention first uses an imidazole acetate solution to swell the fiber surface, and then allows tetraethyl orthosilicate to penetrate into the swollen layer on the fiber surface. After hydrolysis under alkaline conditions, nano-silica particles are formed and anchored within the swollen layer. On one hand, this transforms the smooth surface of the fiber into a rough surface, increasing the bonding force between the fiber and the cement matrix, preventing the fiber from being pulled out of the matrix during cracking under stress and thus failing to fully exert its crack-resistant function. On the other hand, the transition layer composed of the swollen layer and the nano-silica is distributed between the fiber matrix and the cement matrix, effectively preventing the fiber from being broken under stress due to excessive bonding force between the fiber and the cement matrix, thus failing to fully exert its crack-resistant function. This is because the swelling layer is integrated with the fiber matrix, but the force between the two is weakened by the swelling effect of the imidazole acetate, thus constructing a relatively weak bonding layer on the surface of the fiber matrix. The transition layer formed by the fiber and the nano silica particles can both inhibit the easy extraction of fibers from the cement matrix and not completely block the extraction of fibers. Instead, it allows the fibers to be gradually extracted from the cement matrix by slow sliding. This process consumes more energy, effectively improving the crack resistance of the fibers in the cement-based material and enhancing the later strength of the sulfoaluminate cement material of the present invention. Attached Figure Description
[0027] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.
[0028] Figure 1 The image shows a sample of the modified sulfoaluminate cement prepared in Example 1 below.
[0029] Figure 2 The following is a diagram showing the compressive strength test results for Example 1.
[0030] Figure 3 The image shows a sample of the modified sulfoaluminate cement prepared in Example 2 below.
[0031] Figure 4 The image shows a crack-resistant fiber sample prepared in Example 2 below.
[0032] Figure 5 The following is a diagram showing the compressive strength test results for Example 2.
[0033] Figure 6 The image shows a sample of the modified sulfoaluminate cement prepared in Example 3 below.
[0034] Figure 7 The image shows a crack-resistant fiber sample prepared in Example 3 below.
[0035] Figure 8 The following is a diagram showing the compressive strength test results for Example 3.
[0036] Figure 9 The image shows a sample of the modified sulfoaluminate cement prepared in Example 4 below.
[0037] Figure 10 The following is a diagram showing the compressive strength test results for Example 4.
[0038] Figure 11 The image shows a sample of the modified sulfoaluminate cement prepared in Example 5 below.
[0039] Figure 12 The following is a diagram showing the compressive strength test results for Example 5.
[0040] Figure 13 The following is a diagram showing the compressive strength test results for Example 6.
[0041] Figure 14 The image shows a crack-resistant fiber sample prepared in Example 7 below.
[0042] Figure 15 The following is a diagram showing the compressive strength test results for Example 7.
[0043] Figure 16 The image shows a crack-resistant fiber sample prepared in Example 8 below.
[0044] Figure 17 The following is a diagram showing the compressive strength test results for Example 8. Detailed Implementation
[0045] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Experimental methods in the following embodiments, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer.
[0046] Unless otherwise defined, all technical and scientific terms used in this invention have the same meaning as those skilled in the art. The reagents or raw materials used in this invention are readily available through conventional means, and unless otherwise specified, they are used in accordance with conventional methods or product instructions. Furthermore, any methods and materials similar to or equivalent to those described herein can be applied to the methods of this invention. The technical solution of this invention will now be further described in conjunction with the accompanying drawings and specific embodiments.
[0047] Example 1 A preparation process for a sulfoaluminate cement material with high slump retention includes the following steps: (1) Mix sulfoaluminate cement powder with anhydrous ethanol solution containing 0.15wt.% silane coupling agent (KH-560) at a ratio of 1g:3mL and stir evenly. Then heat to 75℃ and keep warm to remove the ethanol to obtain pretreated sulfoaluminate cement.
[0048] (2) The pretreated sulfoaluminate cement is mixed with anhydrous ethanol solution containing 0.07 wt.% tetrabutylphosphine chloride at a ratio of 1 g: 1.5 mL and stirred until homogeneous. Then, the mixture is heated to 60°C and kept at that temperature to remove the ethanol. After completion, 2% of the mass of the pretreated sulfoaluminate cement as polycarboxylate superplasticizer is sprayed in and stirred until homogeneous to obtain modified sulfoaluminate cement (e.g., ...). Figure 1 (As shown).
[0049] (3) Take the following components in the following proportions: 110 parts by weight of modified sulfoaluminate cement, 160 parts by weight of river sand fine aggregate, 12 parts by weight of fly ash with a fineness of 400 mesh, and 0.1 parts by weight of borax. Dry mix the above components for 3 minutes, then add 50 parts by weight of mixing water and continue mixing for 2 minutes to obtain the sulfoaluminate cement material.
[0050] Performance Testing: 1. The flowability of the sulfoaluminate cement material in this embodiment was tested according to the "Method for Determination of Flowability of Cement Mortar" (GBT2419-2005) to measure its slump retention performance. The result was 168 mm. 2. The 28-day compressive strength of the sulfoaluminate cement material in this embodiment was tested according to the "Standard for Test Methods of Physical and Mechanical Properties of Concrete" (GBT 50081-2019). Figure 2 As shown in the figure, the result is 45.11 MPa.
[0051] Example 2 A preparation process for a sulfoaluminate cement material with high slump retention includes the following steps: (1) Mix sulfoaluminate cement powder with anhydrous ethanol solution containing 0.12 wt.% silane coupling agent (KH-550) at a ratio of 1 g: 3.5 mL and stir evenly. Then heat to 80 °C and keep warm to remove the ethanol to obtain pretreated sulfoaluminate cement.
[0052] (2) The pretreated sulfoaluminate cement is mixed with anhydrous ethanol containing 0.06 wt.% tetrabutylphosphine chloride at a ratio of 1 g: 2 mL and stirred until homogeneous. The mixture is then heated to 60°C and kept at this temperature to remove the ethanol. After this process, 1.5% (by weight) of polycarboxylate superplasticizer is sprayed into the pretreated sulfoaluminate cement and stirred until homogeneous to obtain modified sulfoaluminate cement (e.g., ...). Figure 3 (As shown).
[0053] (3) Polyvinyl alcohol fibers (length distribution between 10~30mm, diameter distribution between 0.1~0.15mm) were mixed with a 2.5% (w / w) aqueous solution of 1-ethyl-3-methylimidazolium acetate at a ratio of 1g:0.2mL, stirred evenly, and allowed to stand for 8min. The fibers were then filtered out, washed with water, and dried to remove moisture. The pretreated fibers were then immersed in a mixture of tetraethyl orthosilicate and ethanol at a volume ratio of 1:4 for 45min, with the ratio of pretreated fibers to the mixture being 1g:25mL. After completion, the impregnated fibers were mixed with a 0.05mol / L sodium hydroxide solution at a ratio of 1g:10mL, stirred evenly, and then heated to 60℃ and allowed to stand for 1.5 hours. After completion, the fibers were filtered out, washed with water, and dried to remove moisture to obtain crack-resistant fibers (such as...). Figure 4 (As shown).
[0054] (4) Take the following components in the following proportions: 100 parts by weight of the modified sulfoaluminate cement of this embodiment, 1.785 parts by weight of the crack-resistant fiber of this embodiment, 145 parts by weight of river sand fine aggregate, 10 parts by weight of calcium carbonate powder with a fineness of 300 mesh, and 0.05 parts by weight of sodium gluconate. Dry mix the above components for 3 minutes, then add 44 parts by weight of mixing water and continue stirring for 2 minutes to obtain the sulfoaluminate cement material.
[0055] Performance testing: The fluidity and 28-day compressive strength (e.g., sulphoaluminate cement material of this embodiment) were tested according to the method described in Example 1 above. Figure 5 As shown in the figure, the results are: flowability = 165 mm, 28-day compressive strength = 51.34 MPa.
[0056] Example 3 A preparation process for a sulfoaluminate cement material with high slump retention includes the following steps: (1) The sulfoaluminate cement powder and anhydrous ethanol solution containing 0.18wt.% silane coupling agent (A-171) are mixed at a ratio of 1g:2mL and stirred evenly. Then the mixture is heated to 80℃ and kept warm to remove the ethanol, thus obtaining pretreated sulfoaluminate cement.
[0057] (2) The pretreated sulfoaluminate cement is mixed with anhydrous ethanol solution containing 0.075 wt.% tetrabutylphosphine chloride at a ratio of 1 g: 1 mL and stirred until homogeneous. The mixture is then heated to 60°C and kept at this temperature to remove the ethanol. After this process, 2.2% (by weight) of polycarboxylate superplasticizer is sprayed into the pretreated sulfoaluminate cement and stirred until homogeneous to obtain modified sulfoaluminate cement (e.g., ...). Figure 6 (As shown).
[0058] (3) Polyacrylonitrile fibers (length distribution between 10~30mm, diameter distribution between 0.1~0.15mm) were mixed with a 1.7% (w / w) aqueous solution of 1-allyl-3-methylimidazolium acetate at a ratio of 1g:0.3mL, stirred evenly, and allowed to stand for 12min. The fibers were then filtered out, washed with water, and dried to remove moisture. The pretreated fibers were then immersed in a mixture of tetraethyl orthosilicate and ethanol at a volume ratio of 1:3 for 55min, with the ratio of pretreated fibers to the mixture being 1g:10mL. After completion, the impregnated fibers were mixed with a 0.1mol / L potassium hydroxide solution at a ratio of 1g:6.5mL, stirred evenly, and then heated to 80℃ and allowed to stand for 1 hour. After completion, the fibers were filtered out, washed with water, and dried to remove moisture to obtain crack-resistant fibers (such as...). Figure 7 (As shown).
[0059] (4) Take the following components in the following proportions: 115 parts by weight of the modified sulfoaluminate cement of this embodiment, 3.3 parts by weight of the crack-resistant fiber of this embodiment, 170 parts by weight of river sand fine aggregate, 15 parts by weight of mica powder with a fineness of 500 mesh, and 0.2 parts by weight of sodium hexametaphosphate. Dry mix the above components for 3 minutes, then add 53 parts by weight of mixing water and continue stirring for 2 minutes to obtain the sulfoaluminate cement material.
[0060] Performance testing: The fluidity and 28-day compressive strength (e.g., sulphoaluminate cement material of this embodiment) were tested according to the method described in Example 1 above. Figure 8 As shown in the figure, the results are: flowability = 163 mm, 28-day compressive strength = 54.08 MPa.
[0061] Example 4 A preparation process for a sulfoaluminate cement material with high slump retention includes the following steps: (1) Mix sulfoaluminate cement powder with anhydrous ethanol solution containing 0.07 wt.% tetrabutylphosphine chloride at a ratio of 1 g: 1.5 mL, stir evenly, and then heat to 60°C and keep warm to remove the ethanol. After completion, spray in 2% of the mass of the pretreated sulfoaluminate cement with polycarboxylate superplasticizer, and then stir evenly to obtain modified sulfoaluminate cement (e.g. Figure 9 (As shown).
[0062] (2) Take the following components in the following proportions: 110 parts by weight of modified sulfoaluminate cement, 160 parts by weight of river sand fine aggregate, 12 parts by weight of fly ash with a fineness of 400 mesh, and 0.1 parts by weight of borax. Dry mix the above components for 3 minutes, then add 50 parts by weight of mixing water and continue mixing for 2 minutes to obtain the sulfoaluminate cement material.
[0063] Performance testing: The fluidity and 28-day compressive strength (e.g., sulphoaluminate cement material of this embodiment) were tested according to the method described in Example 1 above. Figure 10 As shown in the figure, the results are: flowability = 142 mm, 28-day compressive strength = 44.13 MPa.
[0064] Example 5 A preparation process for a sulfoaluminate cement material with high slump retention includes the following steps: (1) Mix sulfoaluminate cement powder with anhydrous ethanol solution containing 0.15wt.% silane coupling agent (KH-560) at a ratio of 1g:3mL and stir evenly. Then heat to 75℃ and keep warm to remove the ethanol to obtain pretreated sulfoaluminate cement.
[0065] (2) Spray 2% by weight of polycarboxylate superplasticizer into the pretreated sulfoaluminate cement, and then stir evenly to obtain modified sulfoaluminate cement (e.g. Figure 11 (As shown).
[0066] (3) Take the following components in the following proportions: 110 parts by weight of modified sulfoaluminate cement, 160 parts by weight of river sand fine aggregate, 12 parts by weight of fly ash with a fineness of 400 mesh, and 0.1 parts by weight of borax. Dry mix the above components for 3 minutes, then add 50 parts by weight of mixing water and continue mixing for 2 minutes to obtain the sulfoaluminate cement material.
[0067] Performance testing: The fluidity and 28-day compressive strength (e.g., sulphoaluminate cement material of this embodiment) were tested according to the method described in Example 1 above. Figure 12 As shown in the figure, the results are: flowability = 151 mm, 28-day compressive strength = 44.67 MPa.
[0068] Example 6 A preparation process for a sulfoaluminate cement material with high slump retention includes the following steps: The following components were prepared in the following proportions: 100 parts by weight of the modified sulfoaluminate cement from Example 2 above, 1.785 parts by weight of polyvinyl alcohol fiber (length distribution between 10 and 30 mm, diameter distribution between 0.1 and 0.15 mm), 145 parts by weight of river sand fine aggregate, 10 parts by weight of calcium carbonate powder with a fineness of 300 mesh, and 0.05 parts by weight of sodium gluconate. The above components were first dry-mixed for 3 minutes, then 44 parts by weight of mixing water were added and stirring was continued for 2 minutes to obtain the sulfoaluminate cement material.
[0069] Performance testing: The 28-day compressive strength of the sulfoaluminate cement material of this embodiment was tested according to the method described in Example 1 above (e.g., Figure 13 As shown in the figure, the result is 46.72 MPa.
[0070] Example 7 A preparation process for a sulfoaluminate cement material with high slump retention includes the following steps: (1) Polyvinyl alcohol fibers (length distribution between 10~30mm, diameter distribution between 0.1~0.15mm) were immersed in a mixture of tetraethyl orthosilicate and ethanol at a volume ratio of 1:4 for 45min, and the ratio of pretreated fibers to the mixture was 1g:25mL. After the immersion was completed, the resulting impregnated fibers were mixed with a 0.05mol / L sodium hydroxide solution at a ratio of 1g:10mL and stirred evenly. The mixture was then heated to 60℃ and kept at that temperature for 1.5 hours. After the immersion was completed, the fibers were filtered out, washed with water, and dried to remove moisture, thus obtaining crack-resistant fibers (such as...). Figure 14 (As shown).
[0071] (2) Take the following components in the following proportions: 100 parts by weight of the modified sulfoaluminate cement of Example 2 above, 1.785 parts by weight of the crack-resistant fiber of this example, 145 parts by weight of river sand fine aggregate, 10 parts by weight of calcium carbonate powder with a fineness of 300 mesh, and 0.05 parts by weight of sodium gluconate. Dry mix the above components for 3 minutes, then add 44 parts by weight of mixing water and continue stirring for 2 minutes to obtain the sulfoaluminate cement material.
[0072] Performance testing: The 28-day compressive strength of the sulfoaluminate cement material of this embodiment was tested according to the method described in Example 1 above (e.g., Figure 15As shown in the figure, the result is 47.03 MPa.
[0073] Example 8 A preparation process for a sulfoaluminate cement material with high slump retention includes the following steps: (1) Polyacrylonitrile fibers (length distribution between 10~30mm, diameter distribution between 0.1~0.15mm) are mixed with a 1.7% (w / w) aqueous solution of 1-allyl-3-methylimidazolium acetate at a ratio of 1g:0.3mL, stirred evenly, allowed to stand for 12min, then filtered out, washed with water, and dried to remove moisture, thus obtaining crack-resistant fibers (such as...). Figure 16 (As shown).
[0074] (2) Take the following components in the following proportions: 115 parts by weight of the modified sulfoaluminate cement of Example 3 above, 3.3 parts by weight of the crack-resistant fiber of this example, 170 parts by weight of river sand fine aggregate, 15 parts by weight of mica powder with a fineness of 500 mesh, and 0.2 parts by weight of sodium hexametaphosphate. Dry mix the above components for 3 minutes, then add 53 parts by weight of mixing water and continue stirring for 2 minutes to obtain the sulfoaluminate cement material.
[0075] Performance testing: The 28-day compressive strength of the sulfoaluminate cement material of this embodiment was tested according to the method described in Example 1 above (e.g., Figure 17 As shown in the figure, the result is 50.29 MPa.
[0076] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A preparation process for a sulfoaluminate cement material with high slump retention performance, characterized in that, Includes the following steps: (1) Mix sulfoaluminate cement powder with anhydrous ethanol containing silane coupling agent evenly, and then dry to obtain pretreated sulfoaluminate cement. (2) The pretreated sulfoaluminate cement is mixed evenly with anhydrous ethanol containing tetrabutylphosphine chloride, dried, and then sprayed with polycarboxylate superplasticizer and mixed evenly to obtain modified sulfoaluminate cement. (3) Take the following proportions of raw materials: 100-115 parts by weight of the modified sulfoaluminate cement, 145-170 parts by weight of fine aggregate, 10-15 parts by weight of inorganic filler, and 0.05-0.2 parts by weight of retarder; mix the above raw materials with 44-53 parts by weight of mixing water to obtain sulfoaluminate cement material.
2. The preparation process of the sulfoaluminate cement material with high slump retention performance according to claim 1, characterized in that, In step (1), the ratio of the sulfoaluminate cement powder to the anhydrous ethanol solution is 1g: 2~3.5mL; Alternatively, in step (1), the mass fraction of the silane coupling agent in the anhydrous ethanol solution is 0.12~0.18%; Alternatively, in step (1), the silane coupling agent includes at least one of KH-550, KH-560, A-171, and A-172.
3. The preparation process of the sulfoaluminate cement material with high slump retention performance according to claim 1, characterized in that, In step (2), the ratio of the pretreated sulfoaluminate cement to anhydrous ethanol solution is 1g: 1~2mL; Alternatively, in step (2), the mass fraction of tetrabutylphosphine chloride in the anhydrous ethanol solution is 0.06~0.075%; Alternatively, in step (2), the polycarboxylate superplasticizer is 1.5 to 2.2% of the mass of the pretreated sulfoaluminate cement.
4. The preparation process of the sulfoaluminate cement material with high slump retention performance according to claim 1, characterized in that, In step (3), the inorganic filler includes at least one of fly ash, calcium carbonate powder, and mica powder.
5. The preparation process of the sulfoaluminate cement material with high slump retention performance according to claim 1, characterized in that, In step (3), the retarder includes at least one of borax, sodium hexametaphosphate, sodium pyrophosphate, sodium gluconate, and sodium citrate.
6. The preparation process of sulfoaluminate cement material with high slump retention performance according to any one of claims 1-5, characterized in that, In step (3), the raw materials also include 0.7 to 1.1% of crack-resistant fibers by total mass of sulfoaluminate cement materials.
7. The preparation process of the sulfoaluminate cement material with high slump retention performance according to claim 6, characterized in that, The crack-resistant fiber is prepared by the following method: (i) After mixing polyvinyl alcohol fiber and / or polyacrylonitrile fiber with imidazole acetate solution evenly, the mixture is allowed to stand, and then the fiber is separated and washed to obtain pretreated fiber. (ii) The pretreated fibers are then immersed in a mixture of tetraethyl orthosilicate and ethanol, and the resulting impregnated fibers are mixed with an alkaline solution and then heated and kept at a constant temperature. After completion, the fibers are separated, washed, and dried to obtain the anti-crack fiber.
8. The preparation process of the sulfoaluminate cement material with high slump retention performance according to claim 7, characterized in that, In step (i), the ratio of polyvinyl alcohol fiber and / or polyacrylonitrile fiber to imidazole acetate solution is 1g: 0.2~0.3mL; Alternatively, in step (i), the mass fraction of the imidazole acetate solution is 1.7~2.5%; Alternatively, in step (i), the length of the polyvinyl alcohol fiber and / or polyacrylonitrile fiber is 10~30mm and the diameter is 0.1~0.15mm; Alternatively, in step (i), the settling time is 8 to 12 minutes.
9. The preparation process of the sulfoaluminate cement material with high slump retention performance according to claim 7, characterized in that, In step (ii), the ratio of the pretreated fiber to the tetraethyl orthosilicate-ethanol mixture is 1g: 10~25mL; Alternatively, in step (ii), the volume ratio of the tetraethyl orthosilicate to ethanol is 1:3~4; Alternatively, in step (ii), the immersion treatment time is 45-55 minutes; Alternatively, in step (ii), the alkaline solution includes at least one of sodium hydroxide solution, potassium hydroxide solution, and ammonia solution; Alternatively, in step (i), the imidazole acetate includes at least one of 1-ethyl-3-methylimidazolium acetate, 1-butyl-3-methylimidazolium acetate, and 1-allyl-3-methylimidazolium acetate.
10. The preparation process of the sulfoaluminate cement material with high slump retention performance according to claim 7, characterized in that, In step (ii), the ratio of the impregnated fiber to the alkaline solution is 1g: 6.5~10mL; Alternatively, in step (ii), the concentration of the alkaline solution is 0.05~0.1 mol / L; Alternatively, in step (ii), the heating and heat preservation temperature is 60~80℃, and the standing time is 1~1.5 hours.
Citation Information
Patent Citations
Sulfoaluminate-Portland cement composite system additive, fast-hardening early-strength concrete and preparation method of concrete
CN105884239A
Preparation method of polycarboxylic acid water reducer used for sulphoaluminate cement-based slip-casting material
CN107963825A